التجدد والاستمرار والتحول في الجملة الفعلية وقيمته الأسلوبية عند علماء الأصول المدونة، للإمام مالك (نماذج مختارة) (Faculty of Education Scientific Journal, 2025)
This research dealt with an important aspect of linguistic and fundamentalist studies related to linguistic meaning, and this aspect is one of the most important aspects that emerged from the linguistic and fundamentalist perspective in the Arabic language and in the Qur’an and Sunnah. This study sheds light on the linguistic meaning of the connotations of verbs and their relationship to the Qur’an and Sunnah, through some jurisprudential issues in the Code of Imam Malik, as well as examining similar discussions of the connotations of temporal verbs and others at the grammatical and fundamentalist level, through studying the meaning of the verb in the verbal sentence according to grammarians and scholars of the principles of jurisprudence.
Keywords: Code; renewal; continuity; transformation